Gastronomia no TripAdvisor: O que os Turistas Comentam sobre os Restaurantes de Bonito-MS? Gastronomy on TripAdvisor: What Tourists Comment about Restaurants in Bonito-MS-Brazil? - Silva, Maurílio Barbosa de Oliveira da (2019)
RESUMOAs resenhas eletrônicas, elaboradas e publicadas por consumidores, ganharam importância com o surgimento de novas ferramentas on-line, numa dinâmica em que os setores de turismo, de um modo geral, e gastronomia – em particular – se encontram no centro deste fenômeno. O presente artigo, neste ínterim, tem como objetivo analisar os detalhes em torno dos principais atributos valorizados por turistas que teceram comentários, no TripAdvisor, acerca de restaurantes visitados na cidade de Bonito, no Mato Grosso do Sul [Brasil]. Foram utilizados dados secundários provenientes de 426 comentários e 17.248 verbetes extraídos da página do TripAdvisor no período de janeiro a dezembro de 2017. Para a análise e sistematização dos dados, utilizou-se o software Iramuteq, além de princípios da netnografia. Em suma, percebeu-se que os atributos ‘comida’, ‘serviço’ e ‘ambiente’ mostraram maior frequência nos comentários gerais dos turistas. Estes resultados têm implicações para o setor de restaurantes, pois destacam os determinantes mais importantes da satisfação geral dos turistas.PALAVRAS-CHAVETurismo Gastronômico. Restaurantes. Netnografia. Bonito-MS, Brasil. ABSTRACTThe electronic reviews, elaborated and published by consumers, gained importance with the emergence of new online tools, in a dynamic in which the tourism sector, in general, and gastronomic tourism sector - in particular - are at the center of this phenomenon. This article aims to analyze the details about the main attributes valued by tourists who commented, on TripAdvisor webpage, about restaurants visited in the city of Bonito, in Mato Grosso do Sul State, Brazil. We used secondary data from 426 comments and 17,248 words extracted from the TripAdvisor webpage, in the period from January to December, 2017. For the analysis and systematization of the data, Iramuteq software was used, in addition to the principles of netnography. In summary, we concluded that the attributes ‘food’, ‘service’ and ‘environment’ showed a greater frequency in the general comments of the tourists. These results have implications for the restaurant sector, as they highlight the most important determinants of overall tourist satisfaction.KEYWORDSGastronomic Tourism. Restaurants. Netnography. Bonito-MS, Brazil. AUTORIAMaurílio Barbosa de Oliveira da Silva – Mestrando em Administração, Escola de Administração e Negócios, Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, Brasil. Currículo: http://lattes.cnpq.br/1895257947385340. Orcid: http://orcid.org/0000-0002-8498-3010 E-mail: barbosamaurilio@hotmail.comMaria Clara de Souza Moreira – Mestranda em Administração, Escola de Administração e Negócios, Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, Brasil. Currículo http://lattes.cnpq.br/5843699456090011. Orcid: http://orcid.org/0000-0002-5173-9062. E-mail: mariaclaramoreira_@hotmail.comÁlvaro Gabriel Romero de Souza – Graduando em Administração e bolsista de Iniciação Científica [PIBIC-CNPq], Escola de Administração e Negócios, Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, Brasil. Currículo: http://lattes.cnpq.br/4765451153156430. Orcid: http://orcid.org/0000-0002-6254-2433. E-mail: gabriellowb@gmail.comDyego de Oliveira Arruda – Doutor. Professor na Graduação em Administração e do PPG em Relações Étnico-Raciais, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca, Rio de Janeiro, RJ, Brasil. Currículo http://lattes.cnpq.br/5222976964204691. Orcid: http://orcid.org/0000-0002-9514-284X E-mail: dyego.arruda@gmail.comMilton Augusto Pasquotto Mariani – Doutor. Professor no PPG em Administração, Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, Brasil. Currículo: http://lattes.cnpq.br/0935409945176042. Orcid: http://orcid.org/0000-0001-9485-0150. E-mail: miltmari@terra.com.br REFERÊNCIASBjörk, P. & Räisänen, H. K. (2014). Culinary-gastronomic tourism – a search for local food experiences. Nutrition & Food Science, 44(4), 294-309. LinkBrandt, T.; Bendler, J. & Neumann, D. (2017). Social media analytics and value creation in urban smart tourism ecosystems. Information & Management, 54(6), 703-713. LinkCamargo, B. V. & Justo, A. M. (2013). IRAMUTEQ: um software gratuito para análise de dados textuais. Revista Temas em Psicologia, 21(2), 513-518. LinkCorreia, R. R.; Alperstedt, G. D. & Feuerschutte, S. G. (2017). O uso do método netnográfico na pós-graduação em Administração no Brasil. Revista de Ciências da Administração, 19(47), 163-175. LinkDabija, D. C.; Bejan, B. M. & Tipi, N. (2018). Generation X versus millennials communication behavior on social media when purchasing food versus tourist services. Marketing and Trade, 21(1), 191-205. LinkFagundes, C. & Ashton, M. S. G. (2016). A oferta turística em Bonito, Mato Grosso do Sul, Brasil: o potencial criativo como diferencial competitivo. Rosa dos Ventos – Turismo e Hospitalidade, 8(1), 1-15. LinkFan, Z. P.; Che, Y. J. & Chen, Z. Y. (2017). Product sales forecasting using online reviews and historical sales data: a method combining the Bass model and sentiment analysis. Journal of Business Research, 74, 90-100. LinkFang, B.; Ye, Q.; Kucukusta, D. & Law, R. (2016). Analysis of the perceived value of online tourism reviews: Influence of readability and reviewer characteristics. Tourism Management, 52, 498-506. LinkFragoso, S.; Recuero, R. & Amaral, A. (2011). Métodos de pesquisa para Internet. Porto Alegre: Sulina.Franco, M. C.; Franco, W. C. & Naranjo, M. T. (2017). Análisis de satisfacción: la gastronomía de Samborondón – Ecuador. Estudios y Perspectivas en Turismo, 26(3), 731-745. LinkHall, C. M. & Gossling, S. (2013). Sustainable culinary systems: local foods, innovation, and tourism & hospitality. New York: Routledge.Harrington, R. J.; Ottenbacher, M. C. & Staggs, A. (2012). Generation Y consumers: Key restaurant attributes affecting positive and negative experiences. Journal of Hospitality & Tourism Research, 36(4), 431-449. LinkHeung, V. C. S. & Gu, T. (2012). Influence of restaurant atmospherics on patron satisfaction and behavioral intentions. International Journal of Hospitality Management, 31, 1167-1177. LinkKim, W. G.; Li, J. J. & Brymer, R. A. (2016). The impact of social media reviews on restaurant performance: the moderating role of excellence certificate. International Journal of Hospitality Management, 55, 41-51. LinkKozinets, R. V. (2002). The field behind the screen: using netnography for marketing research in online communities. Journal of Marketing Research, 39(1), 61-72. LinkKozinets, R. V. (2010) Netnography: doing ethnographic research online. California: Sage.Langer, R. & Beckman, S. C. (2005). Sensitive research topics: netnography revisited. Qualitative Market Research: An International Journal, 8(2), 189-203. LinkLee, S. H. & Ro, H. (2016). The impact of online reviews on attitude changes: the differential effects of review attributes and consumer knowledge. International Journal of Hospitality Management, 56, 1-9. LinkLiu, P. & Tse, E. C Y. (2018). Exploring factors on customers’ restaurant choice: an analysis of restaurant attributes. British Food Journal, 120(10), 2289-2303. LinkLiu, Q. B. & Karahanna, E. (2017). The dark side of reviews: The swaying effects of online product reviews on attribute preference construction. MIS Quartely, 41(2), 427-448. LinkMafe, C. R.; Chatzipanagiotou, K. & Perez, R. C. (2018). The role of emotions and conflicting online reviews on consumers' purchase Intentions. Journal of Business Research, 89, 336-344. LinkMak, A. H. N.; Lumbres, M; Eves, A & Chang, R. C. Y. (2017). The effects of food-related personality traits on tourist food consumption motivations. Asia Pacific Journal of Tourism Research, 22(1), 1-20. LinkNakayama, M. & Wan, Y. (2019). The cultural impact on social commerce: A sentiment analysis on Yelp ethnic restaurant reviews. Information & Management, 56(2)1-9. LinkNistoreanu, B. G.; Nicodim, L. & Diaconescu. D. M. (2018). Gastronomic tourism - stages and evolution. 12th International Conference on Business Excellence, 711-717. LinkOMT – Organização Mundial do Turismo. (2017) Segundo informe de la OMT sobre turismo gastronómico: sostenibilidad y gastronomia. LinkOTEB – Observatório do Turismo e Eventos de Bonito/MS. (2017). Anuário Estatístico do Turismo de Bonito – Ano Base 2017. Bonito-MS: Convention & Visitors Bureau. LinkPacheco, L. (2018). An analysis of online reviews of upscale Iberian restaurants. Dos Algarves: A Multidisciplinary e-Journal, 32, 38-53. LinkPantelidis, I. S. (2010). Electronic meal experience: a content analysis of on-line restaurant comments. Food-Service Management, 51(4), 483-491. LinkPark S. & Nicolau, J. L. (2015). Asymmetric effects of online consumer reviews. Annals of Tourism Research, 50, 67-83. LinkPolivanov, B. B. (2013). Etnografia virtual, netnografia ou apenas etnografia? Implicações dos conceitos. Revista Esferas, 2(3), 61-71. LinkRhee, H. T.; Yang, A. B. & Kim, K. (2016). Exploring the comparative salience of restaurant attributes: A conjoint analysis approach. International Journal of Information Management, 36(6), 1360-1370. LinkRojas, R. D. H. & Millán M. G. D. (2018). Turismo Gastronómico: la gastronomía tradicional de Córdoba (España). Estudios y Perspectivas en Turismo, 27(2), 413-430. LinkSanchez-Canizares, S. M. & Lopez-Guzman, T. (2012). Gastronomy as a tourism resource: profile of the culinary tourist. Current Issues in Tourism, 15(3), 229-245. LinkSilva, S. A. (2015). Desvelando a Netnografia: um guia teórico e prático. Intercom - Revista Brasileira de Ciências da Comunicação, 38(2), 339-342. LinkSouza, M. A. R.; Wall, M. L.; Thuler, A. C. M. C.; Lowen, I. M. V. & Peres, A. M. (2018). O uso do software IRAMUTEQ na análise de dados em pesquisas qualitativas. Revista da Escola de Enfermagem da USP, 52, 1-7. LinkTripAdvsor. (2018). Sobre o TripAdvisor. LinkUshizima, L. Y. (2018). Circuitos locais de produção e consumo de alimentos: um olhar sobre o trade turístico de Bonito, MS. Caderno Virtual de Turismo, 18(1), 185-100. LinkVillegas, B. A. (2014). Elaboraciones básicas y platos elementales con carnes, aves, caza: preparación de recetas sencillas. Córdoba: Ideas Propias.Wichels, S. (2014). Nuevos desafíos en Relaciones Públicas 2.0: La creciente influencia de las plataformas de online review en Turismo. Revista Internacional de Relaciones Públicas, 4(7), 197-216. LinkXiang, Z.; Magnini, V. P. & Fesenmaier D. R. (2015). Information technology and consumer behavior in travel and tourism: Insights from travel planning using the Internet. Journal of Retailing and Consumer Services, 22, 244-249. LinkZhang, Z.; Ye, Q.; Law, R. & Li, Y. (2010). The impact of e-word-of-mouth on the online popularity of restaurants: a comparison of consumer reviews and editor reviews. International Journal of Hospitality Management, 26(4), 694-700. LinkZhang, K. Z. K.; Zhao, S. J.; Cheung, C. M. K. & Lee, M. K. O. (2014). Examining the influence of online reviews on consumers' decision-making: A heuristic–systematic model. Decision Support Systems, 67, 78-89. Link PROCESSO EDITORIALRecebido: 11 NOV 18; Avaliado: FEV-MAI; Aceito: 9 JUL 19